Existence and nonexistence of solution of fractional Lam wave equation with polynomial nonlinearity source terms - Mezouar N.; Boulaaras S.; Jan R.; Benramdane A.; Bensaber F. (Elsevier B.V., 2024)
In this work, we examine the existence and nonexistence of solution for lam wave equation with a nonlinear source terms and fractional boundary dissipation. By using the semi group theory approach, we prove the existence of a global solution. Furthermore, we established the blow-up results under the non-positive initial energy condition. 2023 The Author(s)